2018
DOI: 10.3389/fpsyg.2018.02211
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Metacognitive Therapy: A Systematic Review and Meta-Analysis

Abstract: Background: Metacognitive therapy (MCT) continues to gain increased ground as a treatment for psychological complaints. During the last years, several clinical trials on the efficacy of MCT have been published. The aim of the current study was to provide an updated meta-analytic review of the effect of MCT for psychological complaints.Methods: We conducted a systematic search of trials on MCT for young and adult patients with psychological complaints published until January 2018, using PsycINFO, PubMed, the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(144 citation statements)
references
References 53 publications
5
136
0
3
Order By: Relevance
“…Full MCT treatment was first developed for generalized anxiety disorder (Wells, 1995(Wells, , 1997 and subsequently other disorders (Wells, 2000(Wells, , 2009. In meta-analyses, MCT demonstrates large treatment effects and appears potentially more effective or more efficient than cognitive behavioral approaches (Normann et al, 2014;Normann and Morina, 2018). In a direct test of transdiagnostic MCT against disorder-specific CBT across anxiety disorders, outcomes favoring MCT were reported (Johnson et al, 2017) and potential mechanisms of change could be distinguished (Johnson and Hoffart, 2018).…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Full MCT treatment was first developed for generalized anxiety disorder (Wells, 1995(Wells, , 1997 and subsequently other disorders (Wells, 2000(Wells, , 2009. In meta-analyses, MCT demonstrates large treatment effects and appears potentially more effective or more efficient than cognitive behavioral approaches (Normann et al, 2014;Normann and Morina, 2018). In a direct test of transdiagnostic MCT against disorder-specific CBT across anxiety disorders, outcomes favoring MCT were reported (Johnson et al, 2017) and potential mechanisms of change could be distinguished (Johnson and Hoffart, 2018).…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Rumination seems to exacerbate negative mood and could trigger and prolong depression (e.g., Nolen-Hoeksema et al, 2008). MCT could therefore be beneficial for people with depression as suggested by several treatment studies with recovery rates ranging around 70-80% (e.g., Wells et al, 2009Wells et al, , 2012Dammen et al, 2016;Hagen et al, 2017;Normann and Morina, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is a central component in Metacognitive Therapy (MCT) for anxiety and depression (Wells, 2009); however MCT has never been studied in people with chronic pain or elevated PC. Our findings provide a strong rationale for adapting this treatment, which is in some cases more effective than CBT in treating anxiety and depression (Normann & Morina, 2018), for people with chronic pain. This notion of including metacognition as a therapeutic target in pain treatments echoes calls from another recent study which found significant associations between negative metacognition, PC and other pain outcomes (Ziadni et al, 2018).…”
Section: Clinical Implications and Future Researchmentioning
confidence: 82%